A MORPHOLOGICAL ANALYSIS OF WORD FORMATION PROCESS IN MOVIE SCRIPT “THE FLASH” - Devany, Almira; Sopha, Diana (Fakultas Sastra UMN AL Washliyah, 2024)
This study aims to identify the types of word formation processes that appear in the movie script “The Flash” and then to find out the dominant type in the data. The process of word formation is one of the important things to analyze because without realizing it often occurs in daily conversations, as well as in the conversation of a movie. This research uses a qualitative research method. The data used in The Movie script “The Flash” Season 1 Episode 1